Emerging research surrounding power consumption and performance issues in utility computing - Deka, Ganesh Chandra, 1969-; Siddesh, G. M.; Srinivasa, K. G.; Patnaik, L. M.; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, PA 17033, USA) : IGI Global, 2016)
"This book explores methods of treating computing resources and materials as a standard utility, charging customers based on their usage and promoting competition among service providers, covering both benefits and hindrances, as well as theoretical concepts and practical considerations"--Provided by publisher.
GPU implementation of friend recommendation system using CUDA for social networking services / K. G. Srinivasa [and 5 others] -- Software performance estimate using fuzzy based backpropagation learning / Khaleel Ahmad [and 3 others] -- Content based image retrieval system / Mohd Omar, Khaleel Ahmad, M.A. Rizvi -- Dynamic task assignment with load balancing in cloud platform / Subhadarshini Mohanty, Prashant Kumar Patra, Subasish Mohapatra -- Adaptive mobile architecture with utility computing / Robin Singh Bhadoria, Chandrakant Patil -- Face recognition: a tutorial on computational aspects / Alexander Alling, Nathaniel R Powers, Tolga Soyata.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 10/28/2015).
Keywords: Electric utilities -- Management -- Data processing; Electric utilities -- Information technology; Distributed generation of electric power -- Data processing; Electric power consumption -- Data processing; Demand-side management (Electric utilities) -- Data processing; Management information systems; Cloud computing; Dynamic task assignment; High-performance computing; Image retrieval; Power-efficient hardware; Resource management and optimization; Social networking services; Symmetric key cryptography; Electronic books